2020
DOI: 10.1088/1757-899x/881/1/012075
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Study of Radiant Floor Heating Panels Performance at Different Conditions

Abstract: The performance of radiant floor heating panels with different arrangements in room and different room air temperatures are investigated experimentally and numerically. In addition to study the effect of radiant floor heating arrangement on thermal comfort conditions in occupied zone. The room air and panels temperatures are measured at different heights and locations. The temperature of supplying hot water fluctuates from 35 to40 °C. The results present that the different radiant floor heating arrangements ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The reality of heating is complicated, which has different immanent factors (such as heat supply, heating floor structure, envelope structure, room structure and so on) and external factors (such as neighbor situation, outdoor environment, solar radiation, weather condition and so on) 6–8 . The factors are interrelated and all directly or indirectly affect the heating effect of heating system and heat comfort of users.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reality of heating is complicated, which has different immanent factors (such as heat supply, heating floor structure, envelope structure, room structure and so on) and external factors (such as neighbor situation, outdoor environment, solar radiation, weather condition and so on) 6–8 . The factors are interrelated and all directly or indirectly affect the heating effect of heating system and heat comfort of users.…”
Section: Introductionmentioning
confidence: 99%
“…The reality of heating is complicated, which has different immanent factors (such as heat supply, heating floor structure, envelope structure, room structure and so on) and external factors (such as neighbor situation, outdoor environment, solar radiation, weather condition and so on). [6][7][8] The factors are interrelated and all directly or indirectly affect the heating effect of heating system and heat comfort of users. Kassim et al 9 used CFD to conduct numerical simulation of floor heating systems in rooms at different locations, and the results showed that both indoor temperature and the position of floor heating panels affect heat comfort.…”
mentioning
confidence: 99%